What goes up sometimes stays up: Shocks and Institutions as Determinants of Unemployment Persistence - Gianni Amisano; Massimiliano Serati (Tinbergen Institute, 2002)
We analyse the determinants of unemployment persistence in four OECDcountries byestimating a structural Bayesian VAR with an informative priorbased on an insiders/outsiders model. We explicitly insert unemployment ben-efits and labour taxes so that our identification is not affected by the Faust andLeeper (1997) critique. We find widespread hysteresis: demand shocks play adominant role in explaining unemployment also in the medium-run. Moreoverreal wages have low sensitivity to cyclical fluctuations and to labour marketdisequilibria. Our results emphasise the real power of the unions and their in-teractions with structural shocks and other institutions as crucial determinantsof hysteresis.
Keywords: E24; J64; 330; unemployment persistence; insiders-outsiders; hysteresis; structural VAR analysis; Bayesian inference; Arbeitslosigkeit; Natürliche Arbeitslosenquote; Schock; Hysteresis; VAR-Modell; Schätzung; Italien; Schweden; Großbritannien; USA